School Health Development Index (SHDI) as an Instrument for School Health Development (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
This study is a continuation study (second year); in the first year the dimensions and indicators of SHDI had been identified, and now we continue to develop SHDI instrument to find the school health development index. We used an instrumental development method, consisting of; 1) reviewing the concept, dimensions, and indicators of SHDI from the first year’s results, 2) developing blueprint of the instrument, 3) developing instrument’s draft, 4) instrument validation by experts, 5) revising instrument validation results, 6) practitioner testing (UKS teachers), 7) panel testing of instrument, 8) small group trial, 9) final instrument. The results showed that; 1) based on expert review, 90% of the items in the instrument is relevant, 2) from expert test, the instrument of SHDI was approved to be continued, 3) from the panel test there was a change in weightage and addition of health indicators, 4) the trial results showed that the instrument had a sufficient feasibility, and thus could be used to measure SHDI. In the following year we would measure use the instrument in schools to obtain an picture of health school development in Buleleng District.